Statistical methods of discrimination and classification : advances in theory and applications - Choi, Sung C., 1930- (International series in modern applied mathematics and computer science, 1986)
Statistical Methods of Discrimination and Classification: Advances in Theory and Applications is a collection of papers that tackles the multivariate problems of discriminating and classifying subjects into exclusive population. The book presents 13 papers that cover that advancement in the statistical procedure of discriminating and classifying.